Needle Stick Injury among Medical Students: Scoping Review - Laariya, Tira Alfiani; Fauzan Achmad Maliki; Dewi Yuniasih; Fitriana Mawardi (Ahmad Dahlan Medical Journal, 2023)
Needle stick injury (NSI) is one of the occupational hazards in the healthcare sector. Needle stick injury refers to the accident of a percutaneous piercing wound caused by a potentially contaminated instrument with a person’s body fluid. Medical students are high-risk people who contact with needles and body fluids. This study aims to assess the prevalence, incidence, knowledge, awareness, and level of NSI reporting among medical students. Systematic searches were conducted with specific keywords in 4 databases: PubMed, ScienceDirect, Scopus, and Google Scholar databases from 2018 to 2023. A total of eight articles were selected for analysis. They presented descriptively. The study revealed that the prevalence of NSI was varied, ranging from 2,7% to 8%. The incidence rate of NSI was 1,26% to 9,6%. The majority of the studies showed that the knowledge level of medical students was not satisfactory, but they had good awareness and good practice toward needle stick injury prevention. Contrarily, it was found that medical students had a low level of NSI reporting. Hence, it is important to make the medical students understand and aware of NSI, have good practice, and stick to the standardized protocol for NSI, including how to report it correctly.